PENGARUH PROFITABILITAS, LIKUIDITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP STRUKTUR MODAL - Maulana, Yasir; Aziz, Muhhammad Nur (Universitas Dharmawangsa, 2024)
This research aims to test and analyze the influence of profitability, liquidity and institutional ownership on capital structure. The population in this research are property and real estate sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2010-2019 period. Based on the purposive sampling method, 170 data were obtained from 17 property and real estate companies listed on the Indonesia Stock Exchange (BEI) during the 2010-2019 period. The analysis method uses panel data regression analysis, classical assumption testing and hypothesis testing. The research results show that 1) Profitability Ratios measured using ROA have a negative and significant effect on Capital Structure, 2) Liquidity Ratios measured using CR have a negative and significant effect on Capital Structure, 3) Institutional Ownership Ratios measured using KI have a positive and significant effect on Capital Structure. Meanwhile, simultaneously Profitability, Liquidity and Institutional Ownership influence Capital Structure.